The Current Prevalence Rate of Soil-transmitted Helminthiasis in lndonesia - Sutoto Sutoto; Indriyono Indriyono (Indonesian Pediatric Society, 1992)
Surveys on the prevalence rate of soil-transmitted helminthiasis had been done in Indonesia among 12.100 people in 10 provinces at 15 locations in 1990 and 1991. The surveys were meant to obtain data on the recent prevalence rate of soil-transmitted helminthiasis among primary schoolchildren, population in vital productive areas and general community. The results showed that the prevalence rate of Ascaris lumbricoides ranged from 5. 7% to 69.5%, Trichuris trichiura from 0.8% to 53.0% and hookworm from 0% to 24. 7%. The overall prevalence rate of the respective species were 30. 4%, 21.2% and 6.5%. In general, the data of the prevalence rate of soil-transmitted helminthiasis obtained from the recent surveys were lower than those of the surveys done before 1985.